STUDY OF PHENIBUT ANTIEDEMIC ACTION AND NEW GABA DERIVATIVES - T. N. Scherbakova; P. A. Ozerova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
We have studied phenibut, gammalone, and new GABA derivatives action on the development of experimental cerebral edema. We have detected gammoxyn - the most prospective substance for further study as cere-broprotector. We have established that gammoxyn has a signified protective action in cerebral edema.